The Impact of Product Description, Product Photo, Rating, and Review on Purchase Intention in E-commerce - Mokobombang, Muhammad Ghiffary; Kusumawati, Nurrani (Integrasi Sains Media, 2023)
The Covid-19 pandemic in the last 3 years has strengthened E-commerce growth, making online shopping the new norm due to restricted offline activities. To aid buyers and sellers in conducting transactions in E-commerce, E-commerce platforms have introduced features like product descriptions, product photos, ratings, and reviews. These features have created a competitive landscape, benefiting sellers who can use them effectively. Nevertheless, many sellers still struggle to optimize these features and market their products effectively to buyers. Failure to optimize these features correctly restricts the marketing strategy's effectiveness and puts sellers at risk for unanticipated difficulties that may be prevented by determining the various effects of these features on customers’ purchase intentions. Therefore, this research aims to analyze the impact of product descriptions, product photos, and ratings & reviews on customers' purchase intention in E-commerce. A quantitative approach is used in this study, where the data is analyzed through descriptive statistics and PLS-SEM. The result of this study suggested that all three features of product description, product photo, and rating & review significantly and positively influence purchase intention in E-commerce. In addition, the author also found that moderation of perceived trust significantly affects product description and rating & review on purchase intention, while the moderation of perceived risk only significantly affects rating & review on purchase intention. The finding of this research is expected to give insights to E-commerce sellers on optimizing the features in E-commerce to increase the customers’ purchase intention.